1. Not finding help here? Sign up for a free 30min tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Product rule in normed space

  1. Nov 17, 2012 #1
    1. The problem statement, all variables and given/known data
    the product rule fn->f , gn->g implies fngn->fg true in the normed
    vector space (C[0,1],||.||) depends on the the norm||.||. Give a proof or a
    counterexample for (C[0,1],||.||infinite),(C[0,1].||.||1)


    2. Relevant equations
    counterexample , you may wish to examine the case f=g=0 and choose fn=gn for
    some piecewise linear functions.


    3. The attempt at a solution
    what i did for (||.|| infinite) is that ||fn||->||f||, ||gn||->||g|| ,then (||fn||-||f||)*(||gn||-||g||)->0 ,||g||(||fn||-||f||)->0,||f||(||gn||-||g||)->0
    then get (||fn||-||f||)*(||gn||-||g||)+||g||(||fn||-||f||)+||f||(||gn||-||g||)=||fn||*||gn||-||f||*||g||->0
    therefore ||fn||*||gn||->||f||*||g||
    for it is infinite so we get ||fn|||*||gn||=max|fn|*max|gn|=max|fn||gn=max|fngn|=||fngn|| and ||f||*||g||=||fg|| ( by definition of norm) so ||fn*gn||->||fg||
    i dont know it is right or wrong

    and by the (C[0,1],||.||1) i have no idea to get the counterexample
     
    Last edited: Nov 17, 2012
  2. jcsd
  3. Nov 17, 2012 #2
    How would you prove the "product rule" for convergent sequences of real numbers? i.e how do you prove, given [itex]a_n\rightarrow a\in\mathbb{R}[/itex] and [itex]b_n\rightarrow b\in\mathbb{R}[/itex], that [itex]a_nb_n\rightarrow ab[/itex]? Notice that [itex]|\cdot|[/itex] is a norm on the real vector space [itex]\mathbb{R}[/itex].

    What part of that proof (if any) goes wrong if you try to apply it to the normed vector spaces that you're working with?
     
  4. Nov 18, 2012 #3
    i proved the product rule by an->a bn->b then (an-a)(bn-b)->0 and a(bn-b)->0 b(an-a)->0 i.e. (an-a)(bn-b)+a(bn-b)+b(an-a)=anbn-ab->0 . should i prove that ||fn||*||gn||->||f||*||g|| instead of ||fngn||->||fg||??? but if it is , i dont know what is the differences for the case for index infinite and index 1?????
     
  5. Nov 18, 2012 #4

    HallsofIvy

    User Avatar
    Staff Emeritus
    Science Advisor

    I don't see anywhere that you are using the difference between those norms and the usual norm on functions.

    What is the precise definition of those norms?
     
  6. Nov 18, 2012 #5
    for ||fn||1 that is the sum of |fn| , for ||fn||infinte that is the max of |fn|
     
Know someone interested in this topic? Share this thread via Reddit, Google+, Twitter, or Facebook




Similar Discussions: Product rule in normed space
  1. The Product Rule (Replies: 2)

  2. Product rule (Replies: 3)

Loading...